Pengaruh Sistem Merit dan Motivasi terhadap Kinerja Pegawai Dinas P2KBP3A Kabupaten Ciamis - Teti Susilawati; Nana Darna; Ading Rahman Sukmara (Jurnal Manajemen Bisnis Era Digital, 2024)
Employee performance at the P2KBP3A Service is not optimal, which can be seen from the delays in completing work and the work results achieved are not in accordance with the established standards. Then the performance of these employees is also influenced by the merit system which is not optimal, which is caused by the fact that ASN are still found not showing their professionalism in serving the community and an attitude of underestimating work arises because they realize that they have the abilities and expertise that are highly expected and are the mainstay of the leadership. Employee performance is also influenced by motivation which is not optimal, this is caused by the lack of dedication and loyalty of employees in working even though they have received a decent salary and the level of promotion for employees who excel is not optimal. This study aims to study, find out, and analyze (1) The effect of the merit system on the performance of employees at the P2KBP3A Service of Ciamis Regency. (2) The effect of motivation on the performance of employees at the P2KBP3A Service of Ciamis Regency. (3) The effect of the merit system and motivation on the performance of employees at the P2KBP3A Service of Ciamis Regency. This type of research is an explanatory survey, while the technical data analysis is validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression. The results of the study inform that (1) The merit system has a positive effect on employee performance at the P2KBP3A Office of Ciamis Regency. This means that if the merit system is improved, then employee performance at the P2KBP3A Office of Ciamis Regency will also increase. (2) Motivation has a positive effect on employee performance at the P2KBP3A Office of Ciamis Regency. This means that if motivation is improved, then employee performance at the P2KBP3A Office of Ciamis Regency will also increase. (3) The merit system and motivation have a positive effect on employee performance at the P2KBP3A Office of Ciamis Regency.